Исследование влияния объема выборки отсчетов сигнала помехи на пространственную фильтрацию адаптивной антенной решетки - Захарцова, А. В. (ХНУРЭ, 2012)
The analysis of effect of sample size counts for optimum signal interference, according to the criterion of maximum signal/noise ratio, plus the noise characteristics of the output signal of the random lattice for situations uniformly distributed arrivai directions of interference was shown.